Regulation of religious attributes in the Republic of Kazakhstan - Zhangulim, Yerdeshova; Uzduk, Idressova; Ademi, Mukhanova; Marta, Tazhigaliyeva; Zauresh, Saduakhassova (International Journal of Psychosocial Rehabilitation, 2020)
The religious attributes or religious symbols are part of the realization of religion itself. The compliance with the norms and requirements of religions is important for believers. Kazakhstan is one of the countries that practices religious freedom. Therefore, it is important to properly regulate the relationship between individuals and society within the framework of religious freedom and to determine the place of the state in the regulation of religious issues. The relevance of the article is attributable to problems associated with the regulation of religious attributes and realization of the rights of children and adolescents to education in Kazakhstan. The researched religion is Islam, because in Kazakhstan, as in other countries of the world, this issue is controversial. The main goal of our research is to find a balance between the state and civil society, following the examples of more successful states in this area and the implementation of this practice in Kazakhstan taking into account the national peculiarities. Using a comparative legal method help us to analyze national legislation and national practice in the sphere of education and religion, and compare results with foreign legislative framework in similar spheres. To analyse survey materials for research subject we used empirical method. With the help of the method of comparative analysis the experience of different countries were studied in order to identify the best practices regarding the use of religious garment in particular for further use and implementation in Kazakhstan, taking into account national circumstances. The consequences of the ban of religious garment and its impact on the states and societies also were analysed.